(untitled) (International Journal of Environmental Sciences, 2025)
Childhood overweight and obesity are escalating public health concerns globally, particularly in developing nations like India. The shift in dietary patterns and lifestyle is contributing factor for the rise in obesity rates among children. This study investigates the impact of a structured school-based intervention program on the eating habits and physical activity patterns of overweight children aged 6 to 12 years. A total of 506 children from Saharanpur and Roorkee were enrolled using purposive sampling. Pre- and post-intervention data were collected on anthropometric measures, dietary habits, and physical activity using standardized tools. The intervention included educational pamphlets, healthy recipe booklets, and interactive sessions. Anthropometric measurements and eating habits improved statistically significantly after the intervention. The mean waist-to-height ratio (WHtR) and the proportion of children with WHtR > 0.5 decreased statistically significantly after the intervention, indicating that the school-based lifestyle program was successful in lowering central adiposity, encouraging better eating habits, and deterring the use of processed and convenience foods. The impact of focused nutrition education in modifying eating behaviours among overweight school-age children was validated by the observed changes, which were statistically significant across all analysed parameters (p < 0.05). The findings confirms that school-based- interventions are effective in handlingglobal issue of overweight and obesity in children.